KINETIN-MEDIATED ALLEVIATION OF CADMIUM STRESS IN MUNG PLANTS: A COMPREHENSIVE ANALYSIS OF ANTIOXIDANT RESPONSE AND GROWTH ENHANCEMENT - Naveed Ali1, Muhammad Junaid Yousaf1*, Fawziah A. Al-Salmi2, Maha AlHarbi3, Amr Elkelish4, Siham M.AL-Balawi5, Aisha Siddique6, Fawad Ali6*, Imad Gul7, Abdul Manan8 (Chelonian Research Foundation, 2024)
Plants exposed to cadmium (Cd) stress have reduced growth, ineffective photosynthetic rate and poor ability to resist any other environmental calamity. In this study, we aimed to investigate the effect of Kn (kinetin) in alleviating Cd stress in mung plants. Plants of V. radiata were grown in soil contaminated with Cd (100 ppm Cd at 100 /Kg soil) for five days, and then Kn (10 µM) was aerially sprayed onto the leaves in a volume of 10 mL. The plants subjected to Cd stress alone had degraded growth conditions, with RGR, NAR, LAR and TPW reduced by 6.41 %, 59.22 %, 50 % and 6.20 % compared to the control. Interestingly, Kn, an application of synthetic cytokinin, improved growth conditions by 55 % in RGR, 30.12 % in NAR and 19.40 % in LAR and TPW 14 % compared to control. The underlying mechanism for growth enhancement by Kn was the induction of higher antioxidant activity. The Kn-treated seedlings had higher production of antioxidant enzymes such as peroxidase (POD) (50.87 %) and ascorbate peroxidase (APX) (32.61 %) and antioxidant secondary compounds such as TPC (59.21 %), TFC (26.35 %) and proline (28.07 %) compared to the control. This increase in antioxidant activities was due to the complementation of Kn with endogenous IAA (indole-3-acetic acid), GA4 (gibberellic acid) and tZ (trans-zeatin) in the seedlings as these were high in level (30.84 %, 19.21 %, and 35 % respectively) compared to the control. In contrast, these antioxidant activities were reduced in Cd stressed seedlings compared to the control and therefore growth was severely suppressed. Hence, the mechanism of Kn to induce antioxidant activity was due to complementation with endogenous IAA, GA4 and tZ for higher antioxidant response and growth enhancement.